Pengaruh Online Customer Rating, Diskon, Dan Review Service Menu Terhadap Keputusan Pembelian Shopeefood (Studi Kasus Mahasiswa FEB Manajemen Angkatan 2019 Universitas Islam Malang) - Elisyafa Maulidyna; Siti Asiyah; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to identify and analyze the relationship between online customer ratings, discounts, and review service menus on purchasing decisions on Shopeefood. This research used a study on 2019 FEB management students where the data was obtained by distributing questionnaires via g-form to 2019 FEB management students who were selected by purposive sampling. Determining the number of samples in this study used the Malhotra formula and the results obtained were 60 respondents. The analytical method used in this research is instrument test (validity test, reliability test), normality test, classical assumption test (multicollinearity test, heteroscedasticity test), multiple linear regression analysis, hypothesis testing (F test and t test), coefficient of determination test. (Adjusted R2) data processing using the IBM SPSS 25 program. The results of this study indicate that online customer ratings, discounts, and service reviews simultaneously influence purchasing decisions. online customer rating partially has a positive but not significant effect on purchasing decisions, discounts partially has a positive but not significant effect on purchasing decisions, review service menu partially has a significant effect on purchasing decisions. Keywords: Online Customer Rating, Discount, And Service Menu Review, Purchase Decision